Considerations for Effective Laboratory Instruction in Science Classrooms, As Inspired by Metacognition - Wilson, David (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
There are many designs for laboratories that can be effective. Teachers should be able to design labs that are both grounded in methods identified by research as effective, and are efficient for their learning goals and context. Evidence of students’ metacognition should be used to evaluate different lab components and styles. Some merits and limitations of full scale inquiry laboratory styles, simplified inquiry laboratory styles focused on scaffolding specific skills, and some major additions to simple labs are identified. Furthermore, essential components of good laboratory design which are necessary for “meaningful learning” are proposed. The reader will be able to identify what should be considered when choosing a lab style, and components that should be included for meaningful learning.